2012
DOI: 10.1002/nau.22283
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of bladder cancer following diagnosis with bladder pain syndrome/interstitial cystitis

Abstract: This investigation detected a novel association between BC and prior IC/BPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“… 4 , 6 , 7 , 8 One study indicated that IC/bladder pain syndrome (BPS) may contribute to bladder cancer (BC) and an increased risk of BC. 9 Therefore, we predicted that there may be an association between miR-214 and IC. Further analysis suggests that miR-214 is able to target Mitofusin 2 (Mfn2) and mediate the fibrosis process.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 6 , 7 , 8 One study indicated that IC/bladder pain syndrome (BPS) may contribute to bladder cancer (BC) and an increased risk of BC. 9 Therefore, we predicted that there may be an association between miR-214 and IC. Further analysis suggests that miR-214 is able to target Mitofusin 2 (Mfn2) and mediate the fibrosis process.…”
Section: Introductionmentioning
confidence: 99%
“…This implies a possible role of Notch in bladder pathological conditions, beyond cancer, a hypothesis that could be further investigated in human patient samples. It is important to report that patients with IC are 3 times more likely to develop bladder cancer (46), which could of course relate to chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Medical chart summary, medical records of negative urine cytology and urine analysis, and voiding diary are often required for the pre‐review as well. To increase the diagnostic validity of IC, we further ensured that every participant included in the present study group passed the pre‐review to receive a prescription for sodium hyaluronate (Cystistat) . Therefore, there was little possibility for anyone without a clear diagnosis of IC being eligible.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there was little possibility for anyone without a clear diagnosis of IC being eligible. The same methods for the enrollment of IC have already been applied in several published studies …”
Section: Methodsmentioning
confidence: 99%